2013
DOI: 10.1159/000345270
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Delivery of Multiple Collinear Infusion Clouds in Convection-Enhanced Delivery in the Treatment of Parkinson's Disease

Abstract: Background: Delivery of multiple collinear payloads utilizing convection-enhanced delivery (CED) has historically been performed by retraction of a needle or catheter from the most distal delivery site. Few studies have addressed end-infusion morphology and associated payload reflux in stacked and collinear infusions, and studies comparing the advancement with the retraction mode are lacking. Objective: To compare advancement versus retraction mode infusion results. Methods: Infusion cloud pairs were created w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…CED-based in vitro, ex vivo and in vivo animal models have led to active genetherapy trials for treating Parkinson disease (PD)and are supported by histological studies on disease pathology [9].Use of MRI navigation in some clinical trials, helps accurately targeting and providing real time monitoring of viral vector delivery (rCED). Several researcher labs including ours adopted different small and large animal models exploring use of CED in brain [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The results from these studies are promising with a suggestion of superiority over intrathecal (IT) injection.…”
Section: Additionally There Is a Need To Visualize Target And Contrmentioning
confidence: 99%
See 2 more Smart Citations
“…CED-based in vitro, ex vivo and in vivo animal models have led to active genetherapy trials for treating Parkinson disease (PD)and are supported by histological studies on disease pathology [9].Use of MRI navigation in some clinical trials, helps accurately targeting and providing real time monitoring of viral vector delivery (rCED). Several researcher labs including ours adopted different small and large animal models exploring use of CED in brain [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The results from these studies are promising with a suggestion of superiority over intrathecal (IT) injection.…”
Section: Additionally There Is a Need To Visualize Target And Contrmentioning
confidence: 99%
“…Furthermore, the strategies for the movement of an infusion catheter within the target tissue with respect to order of infusion versus movement and catheter design are testable [5]. Commercially available systems for low volume, pressure monitored infusions may also be tested within the surrogate brain to determine infusion pump requirements for planned and future infusion protocols, including operating requirements such as MRI safety of the infusion system [11]. Findings during research on CED catheter design and development of CED stroke treatment lead to the merger of ultra-sound and CED.CED in regard to volume distributed (Vd), volume infused (Vi) and location using in vitro model, ex vivo brain animal models, in vivo insect, mouse, rat, and non-human primate models of PD have been reported in an effort to validate techniques for benchmarking infusion characteristics across models [9,10] and adopted for use in human gene-based therapy trials [10].…”
Section: Additionally There Is a Need To Visualize Target And Contrmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in catheter design 10 , infusion technique 11 , line pressure monitoring 2 , and real time MRI monitoring to correct for brain shift 12,13 , optimize multiple collinear infusions 14 , and monitor for infusate loss 15 have increased the safety and efficacy of the treatment 10 . Additional importance has been placed on the catheter design and infusion strategy including flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a retrospective review of catheter placement on patient outcomes in the PRECISE trial showed that overall catheter placement scores did not correlate with local tumor control, progression free survival, or overall survival 32 . The additional issue of infusion backflow also exists in CED, though catheter design has recently been improved with use of multiple ports, backflow-reducing technology, as well as variable injection rates [33][34][35][36] . Overall, the pattern of drug dispersal during CED, especially around inhomogeneous peritumoral tissue, has proven to be unpredictable 37 , but is steadily improving.…”
mentioning
confidence: 99%